Students' Variation In Translating English Passive Voice Into Bahasa Indonesia - Irwan Irwan; Hendra Eka Putra; Rahmadani Rahmadani (Langkawi: Journal of The Association for Arabic and English, 2018)
This article was focused on analyzing students’ variation in translating English passive voice into Bahasa Indonesia.  The data was taken from the final examination results of Translation I subject.  There were 91 documents. Data were analyzed based on the theory of translation variation.  There were 137 translation variations found after analyzing the students’ translation results. The variations of students’ translations were “(had) being banned” 8 translated variation, “was brought down in” 13 translated variation, “be sentenced” 7 translated variations, “(is) given by” 7 translated variations, “were convicted of” 7 translated variations, “were embroiled in” 5 translated variations, “was placed under” 7 translated variations, “is sponsored by” 4 translated variations, “(was) exposed by” 17 translated variations, “had been covered up by” 5 translated variations, “was banned from” 5 translated variations, “were excluded from” 5 translated variations, “have never been convicted of” 7 translated variations, “(was) banned for” 5 translated variations, “was not suspended” 11 translated variations, “have been banned for” 4 translated variations, “was charged over” 4 translated variations, “were investigated” 2 translated variations, “was caught up in” 4 translated variations.  It can be concluded that the students’ translation skill especially in translating passive voice still have problem and it should be developed as well as possible.